Influence of Clinician-Related Factors on Adherence to the American Heart Association Guidelines for Acute Coronary Syndrome among Clinicians at Kenya Ports Authority clinics in Mombasa, Kenya. - Mailu, Mary Kavinya; Mbugua, Ruth (South East Asia Nursing Research, 2024)
Acute Coronary Syndrome encompasses a spectrum of coronary artery diseases, including Unstable Angina, ST-segment-Elevation Myocardial infarction, and Non-ST Elevation Myocardial Infarction. Standard clinical guidelines like Advanced Cardiac Life Support by American Heart Association are put in place to guide the clinicians in the management of the Acute Coronary Syndrome to improve the outcomes among the patients. The main purpose of the study was to assess influence of clinician-related factors on adherence to the American Heart Association guidelines for Acute Coronary Syndrome among clinicians at Kenya Ports Authority clinics in Mombasa, Kenya. A descriptive cross-sectional study involving quantitative methods of data collection was adopted. The target population was 106 clinicians attending to patients who present with Acute Coronary Syndrome at the KPA clinics in Mombasa. Data analysis was done using Statistical Package for Social Sciences version 25 and presented via graphs, charts, and tables. The study recommends that the KPA management should increase the medical budget to ensure availability of adequate resources for ACS patient management. These resources include adequate staffing, medication, equipment, and staff training costs. The Clinic management should ensure that medications such as aspirin, morphine and nitroglycerine are readily available and accessible at patients care points. The KPA Clinic management to formulate a simple algorithm that outlines the steps to be taken when managing ACS patients. The study further recommends random assessments and post care audits to assess the adherence to ACS guidelines among clinicians.